Commercial sexual exploitation of minors from 1990 to 2005: child prostitution in San José’s Metropolitan area. - Ramírez Hernández, Marcela (2013)
This paper analyzes the problem of commercial sexual exploitation affecting minors, in the definition of child prostitution in the metropolitan center of San José, from a historical perspective. Its objective is to identify and explain how the confluence of economical, social and cultural factors converge in power relationships that have forced some minors to find themselves in situations of sexual exploitation, socially justified and tolerated by the adultcentered and patriarchal predominant system. It also studies the legal actions taken by the Costa Rican government to fight against this problem, and the effects that these actions have gotten in the different forms and spaces used for the children’s and adolescents’ sexual commerce.